PLAINTIFF SUES FOR DIVORCE FROM ABROAD AGAINST DEFENDANT IN INDONESIA - Fachrie Putra Riyadi; Muhamad Rayhan Salman; Reyvaldo Ausyalifa Alfiatna; Shafira Zahru; Agus Dimyati (Ann Publisher, 2026)
Abstract: Background. Based on the authors' experience of various cases handled and resolved in the judicial environment, both in the District Court and the Religious Court, it can be concluded that divorce cases quite dominate the cases filed. Aims. On this basis, the authors became interested in studying more deeply through the writing of scientific journals that focus on the phenomenon of divorce, especially the case of a wife who works as a Female Worker (TKW) in Singapore who filed a divorce lawsuit against her husband in Indonesia. Referring to official data uploaded by the Central Statistics Agency (BPS), there will be 399,921 divorce cases in all regions of the Unitary State of the Republic of Indonesia (NKRI) in 2024. Methods. A normative juridical approach is used in this study which refers to applicable laws and regulations, expert opinions, and empirical data. Result. The results of the study show that both the plaintiff and the defendant have reached an agreement to dissolve their marriage on the grounds that the principle of harmonious and sustainable domestic life as regulated and mandated in the marriage law is no longer fulfilled. Conclusion. Implementation.